The epidemiology underlying age-related avian malaria infection in a long-lived host: the mute swan Cygnus olor - Wood, M; Childs, D; Davies, A; Hellgren, O; Cornwallis, C; Perrins, C; Sheldon, B (2013)
Quantifying the factors that predict parasite outbreak and persistence is a major challenge for both applied and fundamental biology. Key to understanding parasite prevalence and disease outbreaks is determining at what age individuals show signs of infection, and whether or not they recover. Age-dependent patterns of the infection of a host population by parasites can indicate among-individual heterogeneities in their susceptibility to, or rate of recovery from, parasite infections. Here, we present a cross-sectional study of avian malaria in a long-lived bird species, the mute swan Cygnus olor, examining age-related patterns of parasite prevalence and modelling patterns of infection and recovery. One-hundred and fifteen swans, ranging from one to nineteen years old, were screened for infection with Plasmodium, Haemoproteus and Leucocytozoon parasites. Infections with three cytochrome-b lineages of Haemoproteus were found (pooled prevalence 67%), namely WW1 (26%), which is common in passerine birds, and two new lineages closely related to WW1: MUTSW1 (25%) and MUTSW2 (16%). We found evidence for age-related infection in one lineage, MUTSW1. Catalytic models examining patterns of infection and recovery in the population suggested that infections in this population were not life-long - recovery of individuals was included in the best fitting models. These findings support the results of recent studies that suggest hosts can clear infections, although patterns of infection-related mortality in older birds remain to be studied in more detail. © 2013 The Authors.